Efficacy of herbal remedies used by herbalists in Oyo State Nigeria for treatment of Plasmodium falciparum infections a survey and an observation (2004)
In the course of evaluating the contribution of phytomedicine to possible drug discovery of antimalarial drugs, an ethnomedical survey of specialized children traditional clinics was done. In the observational multi center study, efficacy of eight different herbal remedies, each consisting of 3-8 ingredients and administered by herbalists were investigated in clients enrolled in the six traditional clinics in Oyo (urban center) and Otu (rural center) of Oyo State, Nigeria. The clients, aged between six months and fifteen years with clinical symptoms of malaria were enrolled in the clinics of the herbalists, as their usual practice. Oral informed consents were obtained from their parents or guardians. Microscopic diagnosis of malaria infection was used, to evaluate parasitaemia and validate efficacy of herbal remedies. Results of the analyzed shows that, of the 163 clients of the herbalists, only 62 (30 Oyo, 32 from Otu) had microscopically confirmed P. falciparum infection. Only results from 54 clients (29/30 (Oyo) and 25/32 (Otu) with P. falciparurn infection could be evaluated. Plasmodium falciparum infection in 88% (23/29) of clients from Oyo responded to treatment with the herbal remedies while cure rate in clients from Otu was 42% (13/25). Parasite densities ranged from 171 to 53,613 parasites/ul blood and 87 to 36,209 parasites/ul blood in patients from Oyo and Otu respectively. The herbalists administered the remedies and Gossypium arboreum, Anarcudium occidentalis, Citrus medica, Phyllanthus amarus and Lippia multiflora were the main ingredients in the efficacious remedies. The herbalists gave detailed descriptions of each of the 8 herbal remedies proffered. The results confirm the efficacy of two of the eight herbal remedies, thereby validating the role of ethnomedicine as a possible source for the discovery of new cherno-therapeutic agents in the treatment of P. falciparum malaria.